'A source of considerable annoyance': an Israeli–Palestinian backchannel in the efforts to release the blocked Palestinian bank accounts. Issue 4 (1st October 2016) - Heian-Engdal, Marte
Abstract: In addition to the great emotional toll that the Nakba inflicted on the Palestinian people, the 1948 exodus occasioned substantial material losses for the refugees as well. As the 1948 War ground to a halt, the international community had to decide how to deal with all of this, and in the early 1950s the matter of the so-called 'blocked'—or frozen—Palestinian bank accounts became one of the main issues on the UN Palestine Conciliation Commission's agenda. Initially, its effort included the government of Israel and the British-owned Barclays Bank. As things progressed, however, Israeli diplomats also engaged a group of Palestinian refugees in an informal backchannel. This article sheds light on this largely overlooked episode and shows how the channel was established, and how the Palestinian group faced nothing but strong international opposition, most notably from the British Foreign Office. Protecting the interests of its regional ally Jordan, as well as those of Barclays Bank, the Foreign Office did what it could in order to make sure that this particular Israeli–Palestinian backchannel was promptly closed.